2015
DOI: 10.1186/s12917-015-0597-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and biochemical properties of the thoracic aorta in warmblood horses, Friesian horses, and Friesians with aortic rupture

Abstract: BackgroundThoracic aortic rupture and aortopulmonary fistulation are rare conditions in horses. It mainly affects Friesian horses. Intrinsic differences in biomechanical properties of the aortic wall might predispose this breed. The biomechanical and biochemical properties of the thoracic aorta were characterized in warmblood horses, unaffected Friesian horses and Friesians with aortic rupture in an attempt to unravel the underlying pathogenesis of aortic rupture in Friesian horses. Samples of the thoracic aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Harkness et al (1957) investigated the regional elastin and collagen proportions in dogs and found that in the intrathoracic aorta there was approximately twice as much elastin as collagen in the wall; in all other vessels this relationship was reversed. Saey et al (2015) report, for an equine population, a greater concentration of collagen in the distal thoracic aorta compared with proximal; however, there were no significant regional differences in elastin content. Results by Davidson et al (1985) show that elastic fibres were reduced in the abdominal compared with thoracic aorta in a porcine group, and Shadwick (1999) reported higher compliance proximally than distally in whales.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Harkness et al (1957) investigated the regional elastin and collagen proportions in dogs and found that in the intrathoracic aorta there was approximately twice as much elastin as collagen in the wall; in all other vessels this relationship was reversed. Saey et al (2015) report, for an equine population, a greater concentration of collagen in the distal thoracic aorta compared with proximal; however, there were no significant regional differences in elastin content. Results by Davidson et al (1985) show that elastic fibres were reduced in the abdominal compared with thoracic aorta in a porcine group, and Shadwick (1999) reported higher compliance proximally than distally in whales.…”
mentioning
confidence: 80%
“…Saey et al. () report, for an equine population, a greater concentration of collagen in the distal thoracic aorta compared with proximal; however, there were no significant regional differences in elastin content. Results by Davidson et al.…”
Section: Introductionmentioning
confidence: 96%
“…; Saey et al . , ). A primary genetic connective tissue disorder (breed‐specific collagen defect) at an anatomically predisposed site with high pressure gradient in the aortic arch, combined with an additional elastin deficiency and compensatory smooth muscle cell hypertrophy, has been proposed as the causative factor in this pathology (Ploeg et al .…”
Section: Discussionmentioning
confidence: 99%
“…Both Arabian and Friesian horses show an increased prevalence of genetic cardiovascular disorders. Arabians are known for cardiovascular shunting (Bonagura et al 2010;Hall et al 2010), while aortic rupture or aorto-pulmonary fistulation has a higher prevalence in Friesians and occurs generally as a transverse tear adjacent to the scar of the ligamentum arteriosum (van Loon et al 2010;van Loon et al 2011;Ploeg et al 2013;Saey et al 2015Saey et al , 2016. A primary genetic connective tissue disorder (breed-specific collagen defect) at an anatomically predisposed site with high pressure gradient in the aortic arch, combined with an additional elastin deficiency and compensatory smooth muscle cell hypertrophy, has been proposed as the causative factor in this pathology Saey et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent studies have analyzed the morphometric properties of the aorta in horses, including the proportions of elastin, collagen and smooth muscle cells (SMC) [15, 16]. However, they did not examine horses with a broad age range.…”
mentioning
confidence: 99%